1993
DOI: 10.1002/jso.2930530412
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the number of metastatic lymph nodes in gastric cancer with radical surgery

Abstract: To evaluate the effectiveness of extended lymph node dissection in gastric cancer, the relationship between the number of lymph nodes with metastasis and the long-term outcome was studied retrospectively in 761 patients who underwent curative resection with extensive lymph node dissection. The cumulative 5-year survival rate was 85.8% in patients without lymph node metastasis, 60.2% in those with 1-4 lymph nodes, 35.6% with 5-10 nodes, and 12.3% with 11 or more nodes involved. Concerning N2 or N3 patients in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 16 publications
4
28
1
4
Order By: Relevance
“…Therefore we performed a quantitative analysis to determine the status of lymph node metastasis as a prognostic factor in gastric cancer. Previously, we had suggested that the staging of lymph node metastasis should be based on the number of involved lymph nodes [26], and several reports agreed with our suggestion [39][40][41]. The UICC TNM classification revised in 1997 [42] ultimately adopted the number of involved lymph nodes as a parameter for the assessment of lymph node metastatic status, although the cat-egories were rather different from ours.…”
Section: Discussionsupporting
confidence: 45%
“…Therefore we performed a quantitative analysis to determine the status of lymph node metastasis as a prognostic factor in gastric cancer. Previously, we had suggested that the staging of lymph node metastasis should be based on the number of involved lymph nodes [26], and several reports agreed with our suggestion [39][40][41]. The UICC TNM classification revised in 1997 [42] ultimately adopted the number of involved lymph nodes as a parameter for the assessment of lymph node metastatic status, although the cat-egories were rather different from ours.…”
Section: Discussionsupporting
confidence: 45%
“…Lymph node metastasis was reported to be one of the important prognostic factors in patients with gastric cancer [10][11][12]. In patients with T4 gastric cancer, as well as patients with early gastric cancer [13] and those with T3 advanced gastric cancer [14], lymph node metastasis was an important prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 lists the 5-year survival rates of patients with gastric cancer with extragastric lymph node metastasis and shows that the level of lymph node metastasis is associated with survival [22][23][24][25][26][27][28][29][30][31]. The 5-year survival rates of n2 and n3 cases in our series were in accordance with those in the literature, and the 5-year survival rate was significantly different between the n2 and n3 cases in most series, including ours (39% vs 17%; P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 99%